Coyote summer [large type] - Gear, W. Michael (Gear, W. Michael. Saga of the Mountain Sage, 2024)
"Set against the backdrop of the majestic Rocky Mountains and amidst a rich tapestry of Indian cultures--Sioux, Mandan, Crow, Shoshoni--Coyote Summer tells an unforgettable tale of love and reconciliation. Lost in the blowing snow and deep-cold of a Wyoming winter, young Richard Hamilton stumbles south along the foothills of the Big Horn Mountains. Desperate, fighting a battle with starvation and frostbite, Richard drifts closer and closer to disaster, until the day he takes a fall and breaks his rifle. Now, it's but a matter of time. Meanwhile, Willow fights off endless suitors, as she winters with the high mountain Dukurika. And through it all are the growing whispers of witchcraft, which culminate when her Power leads her to Richard's half-frozen body. Saving him will condemn her and leave her adrift and shunned by all people. When White trappers arrive in Richard and Willow's camp with news about a wilderness rendezvous their lives will change forever. And with it comes a decision and a chance for Richard to return to Boston. There he faces a final confrontation with his father, Laura Templeton, and his every dream come true. But then, all choices come at a terrible cost; Coyote plays all people for fools, and Richard must bet everything on one last desperate gamble"--